Comparative analysis of stearates as grease lubricant thickeners. Issue 9 (4th November 2019) - Yao, Lidan; Wang, Lixin; Yang, Haining; Li, Chuan; Song, Hui; Hu, Xianguo
Abstract : Purpose: This paper aims to investigate the influence of stearate types on the thickening ability, dropping point and fiber structure of greases. Design/methodology/approach: Several greases were prepared from polyolefins and various stearates. The melting point of the stearates and the dropping point of the resultant greases were measured, and the intermolecular binding energies of the thickener and the radial distribution function of the metal–oxygen in the thickener were determined with the aid of molecular simulation. The microstructures of the greases were also analyzed via scanning electron microscopy. Findings: A higher stearate binding energy was found to correlate to a higher dropping point of the resultant greases. The thickening ability of the stearate is related to the group and period of the constituent metal ion. Within a group, greater atomic numbers of the metal were correlated to lower thickening ability. In a period, as the atomic number of the metal increased, the thickening ability was enhanced. The radial distribution functions of metal and oxygen can explain the aggregation of the stearate thickeners in the grease. Originality/value: This work compared the thickening capacity of several stearates. Guidelines for preparing stearates to tailor the resultant grease are presented.